2021
DOI: 10.18332/tid/131624
|View full text |Cite
|
Sign up to set email alerts
|

The effect of e-cigarettes on smoking cessation and cigarette smoking initiation: An evidence-based rapid review and meta-analysis

Abstract: INTRODUCTIONElectronic cigarettes, also called e-cigarettes are electronic nicotine delivery systems (ENDS). They can deliver vaporized liquid mainly containing nicotine and propylene glycol through the mouth into the lungs, mimicking the effects of conventional cigarette smoking 1 . Reportedly, the e-cigarette was invented by the Chinese pharmacist Hon Lik in 2003, and internationally patented in 2007 2 . E-cigarettes have been commercially available in Europe and America since 2006 as a cigarette substitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…From 2017 to 2018, e-cigarette use, commonly referred to as vaping, among high school students almost doubled from 11.7 to 20.8% ( Centers for Disease Control and Prevention [CDC], 2019 ). E-cigarettes are marketed as smoking cessation aids, and while there may be some merit to these claims ( Hartmann-Boyce et al, 2021 ; Zhang et al, 2021 ), other studies disagree ( Chen et al, 2020 ) and even point to e-cigarettes as a cause of relapse in former smokers ( Baenziger et al, 2021 ). Furthermore, many young e-cigarette users are “nicotine-naïve,” having never smoked nor used tobacco products before initiating e-cigarette use.…”
Section: It Is Important To Consider the Sensory Aspects Of E-cigaret...mentioning
confidence: 99%
See 1 more Smart Citation
“…From 2017 to 2018, e-cigarette use, commonly referred to as vaping, among high school students almost doubled from 11.7 to 20.8% ( Centers for Disease Control and Prevention [CDC], 2019 ). E-cigarettes are marketed as smoking cessation aids, and while there may be some merit to these claims ( Hartmann-Boyce et al, 2021 ; Zhang et al, 2021 ), other studies disagree ( Chen et al, 2020 ) and even point to e-cigarettes as a cause of relapse in former smokers ( Baenziger et al, 2021 ). Furthermore, many young e-cigarette users are “nicotine-naïve,” having never smoked nor used tobacco products before initiating e-cigarette use.…”
Section: It Is Important To Consider the Sensory Aspects Of E-cigaret...mentioning
confidence: 99%
“…Nicotine use, especially during adolescence, results in short- and long-term detriments to brain development ( Slotkin, 2004 ; Yuan et al, 2015 ; Leslie, 2020 ), reward processing ( Mansvelder et al, 2002 ; Hilario et al, 2012 ; Ren and Lotfipour, 2019 ), and overall health ( Picciotto et al, 2002 ; Lee and Cooke, 2011 ; Kutlu et al, 2015 ). Several studies have also found that initiation of e-cigarette use in adolescence or adulthood increases the likelihood of later combustible cigarette use ( Barrington-Trimis et al, 2016 ; Berry et al, 2019 ; Baenziger et al, 2021 ; Hair et al, 2021 ; Zhang et al, 2021 ), which is alarming considering that smoking remains the leading cause of preventable death and disease in the United States ( Centers for Disease Control and Prevention [CDC], 2020 ). The rapid rise in e-cigarette popularity and subsequent nicotine use, especially among youth, has sparked a public health concern.…”
Section: It Is Important To Consider the Sensory Aspects Of E-cigaret...mentioning
confidence: 99%
“…• (2021) Wang et al: Meta-analysis of 55 observational studies: "As consumer products, in observational studies, e-cigarettes were not associated with increased smoking cessation in the adult population" (Wang, Bhadriraju et al 2021). • (2021) Zhang et al: "Evidence from 9 cohort studies showed that e-cigarette use was not associated with cessation" (Zhang, Bu et al 2021). • ( 2021) WHO: "To date, evidence on the use of ENDS [Electronic Nicotine Delivery Systems] as a cessation aid is inconclusive" (World Health Organization 2021).…”
Section: Recent Reviews Of the Evidence On Cessationmentioning
confidence: 99%
“…A study found that e-cigarette advertising in the U.S contained youth-appealing features [ 28 ]. Research has also shown that e-cigarette use may result in transitions to cigarette smoking [ 29 ], leading to further concerns about how these devices may affect existing disparities in health outcomes related to tobacco. Current research in this regard has not been fully explored; a systematic review found different patterns for e-cigarette awareness, ever use, and current use based on sociodemographic characteristics, highlighting the need to ensure the potential benefits and risks of e-cigarettes do not increase current health disparities [ 30 ].…”
Section: Introductionmentioning
confidence: 99%